Time since fire strongly and variously influences anthophilous insects in a fire‐prone landscape. Issue 9 (3rd September 2019) - Adedoja, Opeyemi; Kehinde, Temitope; Samways, Michael J.
Abstract: Drivers of species productivity and ecosystem function are of great ecological significance. In fire‐prone ecosystems, dispersion patterns of important pollinator species are driven by the various fire events over space and time. However, different species have varying responses to fire intensity and frequency. Here, we assess how time since last fire influences abundance, composition, and dispersion patterns of flowering plants and anthophiles in a highly fire‐prone landscape. We classified study area into age since last fire, which were <1 yr (short‐term burned), 2–3 yr (medium‐term burned), and 9–10 yr (long‐term burned). We collected insect anthophiles using yellow, blue, and white pan traps at sites established in each post‐fire class. We also estimated flower abundance at each study site. Overall, anthophile abundance was highest in medium‐term burned, while lowest in short‐term burned sites. Also, flower abundance was highest at medium‐term burned and lowest in long‐term burned sites. Species composition of flowering plants and anthophiles, especially bees and flies, differed significantly across post‐fire class. Overall, flower abundance had a significant positive effect on bee abundance. Of all the taxa, bees were the only group that showed dispersion patterns reflecting those of flower abundance. Other factors, especially requirements for other resources such as logs, drive the distribution of other anthophile taxa, especially flies. We conclude that fire drives the distribution patterns of bees through its direct effect on flower abundance and composition in a fire‐prone landscape. While high frequency of short‐term fire may reduce flower abundance, flower‐rich areas with moderate time since fire may increase diversity of anthophiles in this fire‐prone landscape.